THE COMPONENTS OF SPEECH EVENTS AND THE USAGE OF LANGUAGE VARIATIONS ON THE CENTRAL CHARACTER IN THE FILM THE GREATEST SHOWMAN - Ardhi Sasongko; Henny Suharyati; Sari Rejeki (Journal Albion : Journal of English Literature, Language, and Culture, 2019)
Abstract   This study discusses the components of events and the use of language variations of the central figure in The Greatest Showman movie (2017). The purpose of this research is to explain how to use speech and the use of language variations of central figures. This study discusses the emergence of speech events and variations in usage on central character. The method used is descriptive qualitative research method with proficient free listening techniques. The results of data analysis show that the speech component always appears for each variety language and there are four languages variations from five different languages. The variety of languages that are often used by central figures is a consultative style, and the variety that is very little used is the formal style and casual style. For the results, it can be concluded that there are 41 variations in the variety of languages found in Michael Gracey's The Greatest Showman movie ; (7) Official variations or variations (Formal); (17) Variations or types of business (Consultative); (7 ) Casual variation or variety, and (8) Intimate variation or variety (Intimate). Of the 41 data found in the film there are 7 formal types with a percentage of 17%, 17 different types of businesses with a percentage of 42%, 7 types of casualties with a percentage of 17% and 10 intimate varieties with a percentage of 20%.Keywords : Sosiolinguistic, components of speech events, language variations, central figure.